2011
DOI: 10.1111/j.1365-263x.2011.01172.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of molar–incisor hypomineralisation observed using transillumination in a group of children from Barcelona (Spain)

Abstract: The population studied showed a prevalence of MIH of 17.8%. The presence of the defect did not differ according to sex in this population. Defects were more common among teeth in the maxilla.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
29
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 31 publications
9
29
4
Order By: Relevance
“…In the present study, the permanent first molars and incisors were both affected in 60% of the cases of MIH, while in 40% only the molars showed hypomineralization (MH). This tendency is also found in other authors2122252627.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In the present study, the permanent first molars and incisors were both affected in 60% of the cases of MIH, while in 40% only the molars showed hypomineralization (MH). This tendency is also found in other authors2122252627.…”
Section: Discussionsupporting
confidence: 88%
“…In Spain, MIH prevalence studies have shown levels of between 12.4% and 21.8%202122. The present study found a slightly higher prevalence level: 24.2%.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Clinical treatment of children is a challenge for the dentist because sensitivity and pain may reduce the child’s cooperation. Moreover, these teeth may be difficult to anesthetize and entail a higher probability of repetitive failure of restoration (2-4). Enamel defects are now acknowledged as risk indicators for dental caries and erosion in children (5-6).…”
Section: Introductionmentioning
confidence: 99%